The role of Social Media in SMEs Sports Sponsorship within the context of The Fourth Industrial Revolution - Mackenzie, Mark (The IIE, 2020)
Artificial Intelligence is predicted to grow immensely from USD$10 billion dollars in 2018 to over USD$126 billion in 2025, (Tractica, 2019). The Fourth Industrial Revolution is transforming the digital market. To optimise their use of the Internet, businesses must understand how The Fourth Industrial Revolution (4IR) will affect this expanding medium. Small and medium enterprises (SMEs) need to better understand the potential advantages of implementing AI-empowered Social Media (SM) marketing to understand how this opportunity could assist with their threat from large firms, (Pauling, 2016). This quantitative study aims to determine how 4IR effects the value of SM in sponsorship campaigns within the context of South African sports SMEs. A closed-ended electronic questionnaire was used to collect statistical data. The results of this research shows there is a moderate, positive relationship with AI usage and SM Value. Indicating if AI usage is increased, the value of SM towards the business may grow. The research shows AI is perceived as important despite a lack of skills in this area. Leading to the recommendation of training staff, and updating policy to the rapidly expanding field.
Keywords: Small and medium enterprises (SMEs); Fourth Industrial Revolution (4IR); Sports sponsorhips; Social media